Excessive daytime sleepiness and gait disturbances in patients with Parkinson’s disease - Xie, Yibo; Zhao, Maoyun; Guo, Yanjie; Tian, Panpan; Liu, Sheng; Xing, Hongxia (Frontiers in Aging Neuroscience, 2025)
BackgroundExcessive daytime sleepiness (EDS), which is common in Parkinson’s disease (PD), has been reported to exacerbate gait disturbance in patients with PD, but there is a lack of objective assessment, as well as an unknown specific mechanism. The purpose of our study is to explore the relationship between EDS and gait parameters.MethodsSixty-one patients with PD were recruited and divided into the EDS group (n = 29) and the non-EDS group (n = 32) based on the scores of the Epworth Sleepiness Scale (ESS). The gait metrics of the two groups were then assessed by wearable devices and compared under various walking scenarios.ResultsCompared with the non-EDS group, the EDS group showed significantly shorter step lengths and stride lengths, slower walk speed and gait speed, reduced shank-max forward swing and sagittal angular velocity, and increased phase coordination indices and mean duration of turns. Pearson correlation analysis revealed a significant association between ESS scores and various gait parameters. Furthermore, multiple linear regression analysis confirmed that EDS is an independent factor influencing gait in patients with PD.ConclusionEDS was independently associated with gait disturbances in patients with PD, suggesting that EDS symptoms warrant serious attention in clinical practice.